'I'm more afraid of racism than of the virus!': racism awareness and resistance among Chinese migrants and their descendants in France during the Covid-19 pandemic. (19th February 2021) - Wang, Simeng; Chen, Xiabing; Li, Yong; Luu, Chloé; Yan, Ran; Madrisotti, Francesco
ABSTRACT: This article focuses on the discrimination and racism experienced by Chinese migrants and their descendants during the Covid-19 pandemic. It analyses this group's increasing awareness and activism toward racial discrimination in French society. The paper is based on an empirical investigation using qualitative and quantitative research methods (online surveys and interviews) with people of Chinese origin living in France. In addition, qualitative data from news media and activists is also crucial to this study because of the important role they play in the social construction of the anti-racism movement. This study shows that the Covid-19 pandemic highlights how the discrimination and racism experienced by people of Chinese origin can take various forms. The epidemic has become a catalyst for Chinese immigration to resist racism, especially among descendants, and among more recent and highly-skilled Chinese immigrants, who have broken their silence, united, and participated in a more activist manner.